Kemampuan Berpikir Kreatif Mahasiswa MBKM Pada Mata Kuliah Perencanaan Pembelajaran - Murniningsih, Murniningsih; Irawati, Ratna Kartika; Eka Putri, Rully Widyanti; Oetomo, R. Andhika (Universitas Negeri Malang, 2022)
This study aims to identify the creative thinking skills of Independent Learning-Independent Campus (MBKM) students in lesson planning lectures at PGSD UST. The method used is quantitative with descriptive analysis. The population in this study were all MBKM students from UNM who took lesson planning lectures with a sampling technique using non-probability sampling, the type of purposive sampling with a total sample of 5 people. The data collection technique used analysis on student assignment documents in the form of a portfolio. The results showed that the creative thinking ability of MBKM students was quite creative with an average of 57.5%. There are 2 or 40% of students who are classified as creative and 3 or 60% of students who are quite creative.